Hyaluronic acid-based gels for oral application: Comparison of in vitro effects on gingival cells and bacteria - Ana F.S. Marques; Neusa Marina Silva; Mariana da Cruz; Joana Marques; António Duarte da Mata (Elsevier, 2024)
Purpose: This study aimed to evaluate the cytotoxic effects of different topical hyaluronic acid-based gels on human gingival fibroblasts and oral bacteria. Methods: Four different hyaluronate gels - Bexident® Aftas (BA), GUM® AftaClear (AfC), Gengigel®(G), Aloclair® Plus (AlC) and a chlorhexidine gel - Bexident®Gums(BG) were selected. Human gingival fibroblasts (HGF) were seeded in 48-well plates with different gel/culture medium concentrations (v/v%) and cell viability was evaluated at 1 and 3 days of culture. Cell morphology was assessed, and alterations graded according to ISO 10993-5:2009(E). Streptococcus oralis CECT 907T colony was, seed on 48-well plate or spread onto the blood agar plates and exposed to the different gel's concentration. The optical density (OD) was assessed, and the diameter of the inhibition zone was measured (mm). Results: BA and G elicited reduced HGF cytotoxicity, followed by AfC. AlC and BG were cytotoxic at concentrations up to 3% for all exposure times. PCM images of HGF showed moderate-to-severe alterations for AlC and BG and slight to mild changes, for BA, AfC and G. The highest antibacterial activity against S.oralis was observed on AlC and AfC, and no antibacterial activity was observed for BA and G. Inhibitory effect in sessile colonies was only observed in AlC and BG. Conclusions: AlC demonstrated superior antibacterial activities against S.oralis but a higher cytotoxic potential in HGF. BA and G presented the lowest cytotoxicity with little to no antibacterial effect. AfC demonstrated bacteriostatic effects and low cytotoxicity on HGF.